1991
DOI: 10.1111/j.1523-536x.1991.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Evaluation of the Content and Quality of Prenatal Care

Abstract: Linkage of measures of the adequacy, content, and quality of prenatal care with pregnancy outcome is a long-standing research challenge. We attempted to improve on prior studies by developing a measure of prenatal care that encompasses the specific items thought to mediate its relationship with birthweight and by then examining the association of this measure with birthweight. An eight-item index of prenatal care was used to abstract information from the medical records of 63 white and 56 black women who gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
8

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
1
12
0
8
Order By: Relevance
“…There have been six studies reported that examine the degree of coverage of recommended health promotion content in prenatal visits, sociodemographic characteristics associated with amount of prenatal health promotion content, and/or birth outcomes Kogan, Alexander, Kotelchuck, Nagey, & Jack, 1994;Kogan, Kotelchuck, Alexander, & Johnson, 1994;Libbus & Sable, 1991;Petitti, Hiatt, Chin, & Croughan-Minihane, 1991;Yu & Jackson, 1995). The lack of consistent health promotion topics and the use of different sociodemographic and outcome measures hamper comparison across these studies.…”
Section: Prenatal Health Promotion Contentmentioning
confidence: 94%
See 1 more Smart Citation
“…There have been six studies reported that examine the degree of coverage of recommended health promotion content in prenatal visits, sociodemographic characteristics associated with amount of prenatal health promotion content, and/or birth outcomes Kogan, Alexander, Kotelchuck, Nagey, & Jack, 1994;Kogan, Kotelchuck, Alexander, & Johnson, 1994;Libbus & Sable, 1991;Petitti, Hiatt, Chin, & Croughan-Minihane, 1991;Yu & Jackson, 1995). The lack of consistent health promotion topics and the use of different sociodemographic and outcome measures hamper comparison across these studies.…”
Section: Prenatal Health Promotion Contentmentioning
confidence: 94%
“…One study found that African American women reported receiving less advice about alcohol and more advice about cigarette and street drug use than Caucasian women (Petitti et al, 1991). The number of topics covered did not relate to LBW after controlling for sociodemographic factors, history of LBW, and low prepregnancy weight.…”
Section: Prenatal Health Promotion Contentmentioning
confidence: 96%
“…Though scant, there has been mixed evidence regarding disparities in the receipt of smoking cessation interventions in prenatal care among pregnant smokers. Some studies have noted that Black pregnant women were more likely to receive provider counseling on interventions for smoking cessation (Petitti et al 1991, Tran et al 2010) while another noted that Black women were less likely to receive provider advice about smoking cessation (Kogan et al, 1994). Thus, exploring associations between provider assistance and maternal characteristics among pregnant smokers may help to information cessation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…25, 40 Another study demonstrated that black women visiting their prenatal care provider received less cessation advice than white women. 41 In contrast, other studies have suggested that black women were more often asked 42 and advised 42,43 about their smoking compared to white women by prenatal care providers. In the present study, control group data showed that black parents were more likely to be asked about tobacco use.…”
Section: Discussionmentioning
confidence: 88%